Description of managerial knowledge for innovation in Argentine micro-SMEs - Gonzalez Marin, Migdlys del Carmen (Revista Universidad de Guayaquil, 2026)
This article presents the results of an exploratory study on the managerial knowledge prevalent in Argentine microenterprises. In-depth interviews were conducted with six business leaders, along with a document review, to describe the managerial knowledge within these businesses. Today’s leaders face complex situations, requiring them to utilize contextual information, process it through knowledge, and translate it into action. This study analyzes managerial knowledge for innovation in Argentine micro-enterprises from a theoretical-epistemological perspective focused on complexity and the apprehension of reality. Through a qualitative study with business leaders, three emerging categories were identified: the apprehension of reality (Zubiri), logos and reason as ordering devices (Foucault), and the understanding of context in the face of uncertainty (Morin). The results move beyond descriptive narratives to propose an analytical approach where managerial knowledge is redefined as a tool for power and strategic adaptation. The study concludes that innovation in complex contexts depends not on technical manuals, but on the leader’s intellectual capacity to translate crises into opportunities for action using managerial tools.